PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN WISATA PARIANGAN DI DESA BATU BINI KECAMATAN PADANG BATUNG KABUPATEN HULU SUNGAI SELATAN - Muhamad Nurrahman Abdi; Hafizianor Hafizianor; Abdi Fithria (Universitas Lambung Mangkurat, 2022)
Perception in a narrow sense means vision, which is how someone sees something, while in a broad sense is a view that is how someone views or interprets something (Harisah & Masiming, 2008). Society is a group of people who get along with each other, in scientific terms, they are interacting with each other. Ecotourism activities are becoming a trend among the public to enjoy different tourist spots than usual. Many tourist objects in South Kalimantan are built based on the environment, such as in watersheds, mountains and coastal areas. One of them is Pariangan tourism which is a river tour and is located in Pariangan Hamlet, Batu Bini Village. This Pariangan tourism object includes the development of new river tourism because it has been managed for about 2 years. This tourism is managed by the community independently and mutual cooperation. Based on this description, a study is needed to determine public perceptions of the development of Pariangan tourism objects. Based on the results of the research, the average public perception is on a scale of 3.89 with a category position of 77.8%, which means that the position of the community perception category is in the